1995
DOI: 10.1148/radiology.195.3.7753988
|View full text |Cite
|
Sign up to set email alerts
|

Nonspecific interstitial pneumonia with fibrosis: radiographic and CT findings in seven patients.

Abstract: Bilateral patchy areas of opacity depicted radiographically and good clinical response to treatment may differentiate NIP from other interstitial pneumonias.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
65
0
4

Year Published

1998
1998
2013
2013

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(77 citation statements)
references
References 0 publications
8
65
0
4
Order By: Relevance
“…Both irregular linear opacities and air-space consolidations have been described as characteristic features (1,4,8). The CT features of NSIP have also been reported (4). In the present study, the predominant CTfeature was interstitial and patchy parenchymal opacification in both lungs predominantly in the middle and lower lung zones.…”
Section: Case Reportsupporting
confidence: 78%
See 2 more Smart Citations
“…Both irregular linear opacities and air-space consolidations have been described as characteristic features (1,4,8). The CT features of NSIP have also been reported (4). In the present study, the predominant CTfeature was interstitial and patchy parenchymal opacification in both lungs predominantly in the middle and lower lung zones.…”
Section: Case Reportsupporting
confidence: 78%
“…According to those reports, it is suggested that 10-20% of patients with NSIP died because of respiratory failure. Since NSIP has been described only recently, knowledge of its radiographic manifestations is limited ( 1,4,8). Both irregular linear opacities and air-space consolidations have been described as characteristic features (1,4,8).…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…(HandE,xlOO) limited [13]. Recently, radiographic and high resolution CT findings of the disease were de scribed [14]. However, this report included only sevencasesof the disease.Furthermore, we know of no reports on correlation of high resolution CT' and pathologic findings.…”
mentioning
confidence: 99%
“…Many reports have described that corticosteroids are effective for NSIP (1)(2)(3)(4)(5)(6)(7)(8)(9). In addition, although other immunosuppressants (such as cyclophosphamide or azathioprine), have been used in patients with NSIPin whomcorticosteroids were ineffective, the role of these immunosuppressants in patients with NSIP has not been clarified (1,(5)(6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%